Numerical Analysis of The Effect of Chine Variation on The Design of The Senopati Catamaran Fishing Boat on Resistance Based on Maxsurf Resistance Software - Fiqri Fadillah Fahmi; Aldias Bahatmaka; Rizqi Fitri Naryanto; Lee Sang Won (Jurnal Inovasi Mesin, 2025)
The majority of fishermen in Indonesia still rely on traditional boats that have been built and passed down through generations. These fishermen tend to focus primarily on maximizing their catch, often overlooking other important aspects such as hydrodynamic resistance. In reality, beyond the fishing gear used, one of the key factors influencing the effectiveness of a fishing vessel is its hull design. This study aims to analyze the resistance characteristics of a catamaran-type fishing vessel designed by the Senopati Team. The analysis was conducted using Maxsurf Resistance software with speed variations ranging from 1 to 15 knots. To determine the optimal resistance performance, chine variations were introduced to the hull design, including both single and double chine configurations. Each variation applied chine widths of 5%, 6%, and 7% of the vessel's beam, with chine heights of 1.1 meters and 1.4 meters. The analysis results indicate that resistance increases with vessel speed. However, an increase in chine width generally leads to a reduction in resistance. The most optimal hull configuration was identified as the single chine with 7% width and 1.4 meters height. These findings suggest that the incorporation of chine variations, whether single or double, can effectively reduce the resistance experienced by the vessel compared to a bare hull configuration.